A 2-Minute Cognitive Screener for Predicting 1-Year Functional Recovery and Survival in Older Adults After Hip Fracture Repair. Issue 1 (3rd June 2021) - Fortes-Filho, Sileno de Queiroz; Aliberti, Márlon Juliano Romero; Melo, Juliana de Araújo; Apolinario, Daniel; Sitta, Maria do Carmo; Suzuki, Itiro; Garcez-Leme, Luiz Eugênio
Abstract: Background: Implementing cognitive assessment in older people admitted to hospital with hip fracture—lying in bed, experiencing pain—is challenging. We investigated the value of a quick and easy-to-administer 10-point Cognitive Screener (10-CS) in predicting 1-year functional recovery and survival after hip surgery. Methods: Prospective cohort study comprising 304 older patients (mean age = 80.3 ± 9.1 years; women = 72%) with hip fracture consecutively admitted to a specialized academic medical center that supports secondary hospitals in Sao Paulo Metropolitan Area, Brazil. The 10-CS, a 2-minute bedside tool including temporal orientation, verbal fluency, and three-word recall, classified patients as having normal cognition, possible cognitive impairment, or probable cognitive impairment on admission. Outcomes were time-to-recovery activities of daily living (ADLs; Katz index) and mobility (New Mobility Score), and survival during 1-year after hip surgery. Hazard models, considering death as a competing risk, were used to associate the 10-CS categories with outcomes after adjusting for sociodemographic and clinical measures. Results: On admission, 144 (47%) patients had probable cognitive impairment. Compared to those cognitively normal, patients with probable cognitive impairment presented less postsurgical recovery of ADLs (77% vs 40%; adjusted sub-hazard ratio [HR] = 0.44; 95% confidence interval [CI] = 0.32–0.62) and mobility (50% vs 30%; adjusted sub-HR = 0.52; 95% CI = 0.34–0.79), and higher risk of death (15% vs 40%; adjusted HR = 2.08; 95% CI = 1.03–4.20) over 1-year follow-up. Conclusions: The 10-CS is a strong predictor of functional recovery and survival after hip fracture repair. Cognitive assessment using quick and easy-to-administer screening tools like 10-CS can help clinicians make better decisions and offer tailored care for older patients admitted with hip fracture.